The Democratic Window of Opportunity: Evidence from Riots in Sub-Saharan Africa - Toke Aidt; Gabriel Leon (Center for Economic Studies and ifo Institute (CESifo), 2014)
We show that drought-induced changes in the intensity of riots lead to moves towards democracy in sub-Saharan Africa, and that these changes are often a result of concessions made as a result of the riots. This provides evidence that low-intensity conflict can have a substantial short-run impact on democratic change, and supports the .window of opportunity. hypothesis: droughts lead to an increase in the threat of conflict, and incumbents often respond by making democratic concessions.
Keywords: D70; P16; 330; riots; drought; transitions; democracy; autocracy